2017
DOI: 10.3389/fneur.2017.00026
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Noisy Galvanic Vestibular Stimulation on Ocular Vestibular-Evoked Myogenic Potentials to Bone-Conducted Vibration

Abstract: ObjectiveGalvanic vestibular stimulation (GVS) delivered as zero-mean current noise (noisy GVS) has been shown to improve static and dynamic postural stability probably by enhancing vestibular information. The purpose of this study was to examine the effect of an imperceptible level noisy GVS on ocular vestibular-evoked myogenic potentials (oVEMPs) in response to bone-conducted vibration (BCV).Materials and methodsoVEMPs to BCV were measured during the application of white noise GVS with an amplitude ranging f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
(42 reference statements)
1
17
0
Order By: Relevance
“…Currently, the therapeutic regime in individuals with BVH is limited to physical therapy ( 39 ), where approximately only half of these patients benefit from this kind of intervention ( 40 ). The findings we report in this study, together with previous reports on nGVS-induced improvements in balance control as well as ocular-motor function ( 41 ) can promote an alternative or additional therapeutic option for reducing the postural imbalance and incidence of falls in this population.…”
Section: Discussionsupporting
confidence: 78%
“…Currently, the therapeutic regime in individuals with BVH is limited to physical therapy ( 39 ), where approximately only half of these patients benefit from this kind of intervention ( 40 ). The findings we report in this study, together with previous reports on nGVS-induced improvements in balance control as well as ocular-motor function ( 41 ) can promote an alternative or additional therapeutic option for reducing the postural imbalance and incidence of falls in this population.…”
Section: Discussionsupporting
confidence: 78%
“…Studies have shown that patients with vestibular disorders have increased COP sway path lengths and mean velocities [ 21 ] and that nGVS can enhance the function of vestibular afferents [ 22 ]. These findings suggest that the improved function of vestibular afferents may have reduced COP sway observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the improved function of vestibular afferents may have reduced COP sway observed in this study. The rationale for these ameliorating effects of nGVS is considered to be stochastic resonance [ 22 ], a phenomenon where a signal that is too weak to exceed a given threshold is amplified by adding noise. Stochastic resonance appears to enhance information processing in the sensory system [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that a 30-s application of nGVS can improve postural stability in healthy subjects and in BV patients ( 12 ). nGVS also enhances the vestibulo-ocular reflex in healthy subjects ( 13 ) and the vestibulo-spinal reflex in healthy subjects and BV patients ( 14 ). Moreover, nGVS improves walking stability in healthy subjects and BV patients ( 15 17 ).…”
Section: Introductionmentioning
confidence: 99%